On the Issue of Machine-Building Industry Production Quality Development - Tamaryan, Grigor (Bulletin of Yerevan University G: Economics, 2012)
The issues of the quality control and development with the focus on machine-building industry production are mainly discussed in the article. Taking into account the current role and importance of technologies and necessity of quality development in conditions of free market economy and competition, quality control becomes major approach to assure the role of national production in the world market. That is why such countries as Armenia and Russian Federation adopt internationally recognized certification systems of the quality assurance for the national machine-building industry production.